(NkRASNOZNAMENNYJ ~ERNOMORSKIJ FLOT (B/s - (NzOTKIN(B, (Nn(B. (Nf(B.s; (Nl@B^IKOW(B, (Nm(B. (Na(B.s; (NbOLGARI(B, (Np(B. (Np(B.s ((NmOSKWA (B:s (NwOENIZDAT(B,s, 1987)
(NuKAZ(B. (NIMEN(B, (NKORABLEJ I SUDOW(B: (NS(B. 318-334s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (N~ERNOMORSKIJ WOENNO(B-(NMORSKOJ FLOT (B- (NiSTORIQs; (N~ERNOMORSKIJ FLOTs